1972
DOI: 10.1111/j.1399-3054.1972.tb03579.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Amounts of Chloroplast and Cytoplasmic Ribosomal‐RNAs and Photomorphogenesis in Dryopteris Gametophytes

Abstract: The basis for the difference in total-RNA base composition between the filamentous and the prothallial gametophytes of the fern Dryopteris has been examined. Analyses of the relative amounts of chloroplast rRNA {i.e.^M°^°P^^" -'^-^^^ ) indicate a shift to a higher chloroplast + cytoplasmic rRNA level of chloroplast rRNA in the transition from filamentous to prothallial growth. This increased level of chloroplast rRNA is of sufficient magnitude to be entirely responsible for the observed change in total-RNA bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…For instance, after a transfer from red to blue light, fern filaments undergo a rapid transition to two-dimensional growth. But Howland (1972) demonstrated that an increase in the relative level of plastid rRNA accounts for this observed shift in RNA base composition. Hotta ( 1960) observed that the RN As of two-dimensional gametophytes have higher proportions of the nucleic acid bases guanine and cytosine than do the RNAs of filamentous gametophytes.…”
mentioning
confidence: 99%
“…For instance, after a transfer from red to blue light, fern filaments undergo a rapid transition to two-dimensional growth. But Howland (1972) demonstrated that an increase in the relative level of plastid rRNA accounts for this observed shift in RNA base composition. Hotta ( 1960) observed that the RN As of two-dimensional gametophytes have higher proportions of the nucleic acid bases guanine and cytosine than do the RNAs of filamentous gametophytes.…”
mentioning
confidence: 99%
“…However, little attention was paid to this point in previous works (SCHRAUDOLI MILLER, 1968;BURNS andINGLE, 1968, 1970;DAVIS, 1968DAVIS, , 1970SCHRAUDOLF and LEGLER, 1969;HOWLAND, 1972). On the contrary, the influences of the inhibitors o n the orientation of the cell plate were successfully examined for the first time under a microscope using an appropriate experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…BEKCFELD (1964) also pointed out that much of the blue-light-induced protein synthesis resulted from chloroplast development. Lately, evidence has accumulated against the hypothesis (SOBOTA andPARTANW, 1966, 1967;SCHRAUDOLF, 1967;MILLER, 1968;DAVIS, 1968DAVIS, , 1970BURNS andINGLE, 1968,1970;SCHRAUDOLF and LEGLER, 1969;HOWLAND, 1972).…”
mentioning
confidence: 99%
“…These changes have been studied in detail in only a few instances. In a timelapse study of Dryopteris [ilix-mas, Howland ( 1972) concluded that the newly synthesized wall on the flanks as well as at the extreme tip of the apical swelling had been formed after the plants had been transferred from red to blue light; cell wall produced prior to blue light exposure was not involved in the cell expansion. This apical swelling was associated with a reduction in the rate of elongation (Davis, 1969).…”
mentioning
confidence: 99%
“…Certain biochemical changes occur later (Drumm and Mohr, 1967;Howland, 1972); therefore, these events cannot be part of the mechanism leading to the morphological change. Certain biochemical changes occur later (Drumm and Mohr, 1967;Howland, 1972); therefore, these events cannot be part of the mechanism leading to the morphological change.…”
mentioning
confidence: 99%